Analisis Peran Lembaga Keuangan (Pegadaian) Terhadap Pengembangan Perekonomian Masyarakat Umum (Usaha Umkm) (Universitas Gresik, 2023)
Pawnshops have recently become a permanent fixture in the lives of ordinary Indonesians. Jewelry, tools, and other property are pawned daily to temporarily add to the expenses of those unable to borrow from banks and other financial institutions. Moreover, some of these pawnshops have penetrated the provinces, so they have taken on a new role as development exponents. But despite its popularity, the study of pawnshops is not that important. Therefore, this paper tries to fill the gap by presenting several new facts related to the continuous existence of pawnshops in the financial system. This research was studied through a descriptive approach with data access from library research, so this research was studied qualitatively. It then discusses the role of pawnshops in the financial system. This is followed by an analysis of the pawnshop's performance with particular emphasis on sources and uses as well as the profitability and operational efficiency of the pawnshop. To find out whether the pawnshop is still able to increase its competitive advantage by increasing its size, tests are run on economies of scale. In conclusion, what all the analysis and results show means that pawnshops are also capable of being a good alternative source of credit for small offerings for MSMEs and the public.